Effective Volumes of Waters of Crystallization: Ionic Systems - Glasser, Leslie (AMER CHEMICAL SOC, 2019)
© 2019 American Chemical Society. We investigate the effective molecular volumes of waters of crystallization for 182 ionic materials as a function of their degree of hydration (the "effective" volume being the difference per water of hydration between the formula unit volumes of hydrates, including the parent anhydrate). We establish a median effective H2O molecular volume of 0.024(2) nm3, a value which is somewhat smaller than the ambient molecular volume of liquid water, 0.0299 nm3. The effective water of crystallization volumes increase slightly as the degree of hydration increases toward an apparent upper limit of about 18 water molecules, as is also observed in the behavior of the Gibbs energies of hydration. Our data include not only common ionic solids with inorganic anions but also organic anions and the zwitterionic l-amino acids; their effective volumes are commensurate with the values for the common ionic solids and thus also close to the molecular volume of liquid water. We provide two examples of the application of these principles to organic systems, yielding similar values for the effective volume of hydration. We demonstrate how these volumes may be used in the prediction of various thermodynamic values of hydrates and their parent anhydrates.